2009
DOI: 10.1016/j.jmb.2009.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Globular Tetramers of β2-Microglobulin Assemble into Elaborate Amyloid Fibrils

Abstract: Amyloid fibrils are ordered polymers in which constituent polypeptides adopt a non-native fold. Despite their importance in degenerative human diseases, the overall structure of amyloid fibrils remains unknown. High-resolution studies of model peptide assemblies have identified residues forming cross-β-strands and have revealed some details of local β-strand packing. However, little is known about the assembly contacts that define the fibril architecture. Here we present a set of three-dimensional structures o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

9
90
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 60 publications
9
90
1
Order By: Relevance
“…Analysis of the structure of acid-unfolded V L domains by NMR spectroscopy further revealed the AL1 peptide segment to be largely unfolded in the V L domain of Wil AL protein under oxidative conditions and to be significantly structured within two control V L domains that originated from LCs not associated with AL amyloidosis (31). It is also interesting to note that the V L Ig domain is topologically related to the β-sandwich structure of β2-microglobulin, another protein that can give rise to amyloid inside the body and that was analyzed with cryo-EM (13). However, the pattern of amyloidogenic sites is different in β2-microglobulin and may not substantially depend on the strand, which is topologically homologous to strand C within V L domains (15) studied here.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Analysis of the structure of acid-unfolded V L domains by NMR spectroscopy further revealed the AL1 peptide segment to be largely unfolded in the V L domain of Wil AL protein under oxidative conditions and to be significantly structured within two control V L domains that originated from LCs not associated with AL amyloidosis (31). It is also interesting to note that the V L Ig domain is topologically related to the β-sandwich structure of β2-microglobulin, another protein that can give rise to amyloid inside the body and that was analyzed with cryo-EM (13). However, the pattern of amyloidogenic sites is different in β2-microglobulin and may not substantially depend on the strand, which is topologically homologous to strand C within V L domains (15) studied here.…”
Section: Discussionmentioning
confidence: 99%
“…The common structural motif of all these fibrils is an intermolecular stack of β-strands, termed the fibril cross-β conformation (3). Previous analyses with NMR, electron cryomicroscopy (cryo-EM), and other techniques have provided information on the assembly of the polypeptide chains in the fibril and illuminated the residue-specific conformation (4)(5)(6) and overall properties of these fibrils, such as their handedness, polarity, and symmetry (7)(8)(9)(10)(11)(12)(13). By contrast, it has remained difficult to determine the orientation and assembly of the polypeptide chains relative to one another and the intermolecular interactions between the molecules within a full-scale fibril.…”
mentioning
confidence: 99%
“…Previous studies have shown that these fibrils possess a parallel in register cross-β structure (29,30) assembled into multidomain filaments coiled together, described by cryo-EM (28). These fibrils bind amyloid-specific ligands such as serum amyloid P component with a similar affinity to their ex vivo counterparts (31).…”
mentioning
confidence: 92%
“…Here, we use β 2 m amyloid fibrils formed in vitro as a model system to investigate the structural basis of membrane damage by amyloid fibrils (27,28). Previous studies have shown that these fibrils possess a parallel in register cross-β structure (29,30) assembled into multidomain filaments coiled together, described by cryo-EM (28).…”
mentioning
confidence: 99%
“…Low-resolution details of intact amyloid fibrils, which can be generated by electron microscopy (EM) [17], cryo-EM [18], and atomic force microscopy (AFM) [19,20], have shown that fully assembled amyloid fibrils may contain different numbers of protofilaments, either intertwined into helices or bound side-to-side in a twisted ribbon structure [21,22], in which the ␤-strands are arranged perpendicular to the fibril axis.…”
mentioning
confidence: 99%